1991
DOI: 10.1093/milmed/156.3.118
|View full text |Cite
|
Sign up to set email alerts
|

Functional Restoration Following Anterior Cruciate Ligament Reconstruction in Active-Duty Military Personnel

Abstract: A retrospective review was conducted of 112 active-duty military patients receiving anterior cruciate ligament reconstruction between 1985 and 1987. Mean age of these patients was 26.4 years, average follow-up was 2.35 years, and the average interval from time of injury to reconstruction was 13.6 months. The three most commonly employed surgical techniques were the Andrews' iliotibial band tenodesis, mid-third patellar tendon autograft, and a combined Andrews' and mid-third patellar tendon reconstruction. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
2
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
4
2
0
1
Order By: Relevance
“…Thompson and Fu [35] suggest that the subtle alteration in knee joint kinematics caused by meniscectomy creates an unfavorable condition for the ACL reconstructed knee. Despite these limitations in documenting previously injured knee structures our results generally concur with those of previous authors [8,15,30] who have also found that a greater incidence of injured structures in the knee at the time of ACLR was associated with higher levels of participation restrictions. As a result we recommend that injury history be routinely examined in patients with a history of ACLR, as this information may be helpful in establishing a patient's prognosis.…”
Section: Reliabilitysupporting
confidence: 91%
See 1 more Smart Citation
“…Thompson and Fu [35] suggest that the subtle alteration in knee joint kinematics caused by meniscectomy creates an unfavorable condition for the ACL reconstructed knee. Despite these limitations in documenting previously injured knee structures our results generally concur with those of previous authors [8,15,30] who have also found that a greater incidence of injured structures in the knee at the time of ACLR was associated with higher levels of participation restrictions. As a result we recommend that injury history be routinely examined in patients with a history of ACLR, as this information may be helpful in establishing a patient's prognosis.…”
Section: Reliabilitysupporting
confidence: 91%
“…Researchers also recommend assessing the status of knee structures, activity limitations, and impairments in patients with a history of ACLR [1,7,8,13,15,20], presumably because these factors provide some estimate of participation restrictions following ACLR. Knee structures are the anatomical components of the knee [3,32].…”
mentioning
confidence: 99%
“…Patients in general complied well with the post‐operative rehabilitation confirmed with the excellent results of isokinetic strength testing. This feature of good compliance with rehabilitation in older patients has been previously recognised [11, 16]. The reduction in re‐injury rate was considerable, with only one patient (3%) in our series suffering three re‐injuries post‐operatively.…”
Section: Discussionsupporting
confidence: 74%
“…[63][64][65] Furthermore, predictors of a worse outcome in this population include subsequent surgeries, severe chondromalacia at the time of surgery, need for a revision surgery, and a combined multiligamentous injury. 63,65,66 These limitations are further magnified in those occupations that are considered to be combat support roles. 63 While the short term-outcomes of ACL are good, there is particular concern amongst the military population that the posttraumatic cartilage effects at the time of ACL injury lead to a high degree of posttraumatic osteoarthritis requiring eventual treatment.…”
Section: Discussionmentioning
confidence: 99%